1996
DOI: 10.1248/cpb.44.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of 1268 nm Emission for Comparison of Singlet Oxygen (1.DELTA.g) Production Efficiency of Various Dyes.

Abstract: Singlet oxygen generation from laser-excited photosensitive dyes was measured directly using a sensitive near-infrared emission spectrometer to monitor the O2(1 delta g)-->O2(3 sigma -g) transition at 1268 nm. The emission intensity was proportional to both the laser power and the concentration of the dyes. The singlet oxygen producing ability of the dyes was compared with that of eosin YS as a standard in methanol. The relative efficiencies of singlet oxygen generation were determined for rose bengal, erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 2 publications
1
19
0
Order By: Relevance
“…[17][18][19][20][21][22] 8,14) Our previous results showed that the activity levels of CYP2A6 and UGT in bovine liver microsomes were similar to human liver microsomes 4,28,29) but differed from rat microsomes, as rat microsomes did not involve CYP2A6 activity. Thus, it was considered that bovine microsome data were very similar to human microsome data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21][22] 8,14) Our previous results showed that the activity levels of CYP2A6 and UGT in bovine liver microsomes were similar to human liver microsomes 4,28,29) but differed from rat microsomes, as rat microsomes did not involve CYP2A6 activity. Thus, it was considered that bovine microsome data were very similar to human microsome data.…”
Section: Discussionmentioning
confidence: 99%
“…16) Meanwhile, phenyl-xanthene dyes, such as rose bengal (RB), ET, phloxine (PL), eosin (ES), uranine (UR), rhodamine (RM), and fluorescein are known as light-enhancing reagents (catalytic light reaction) by the generation of 1 O 2 on those dyes. [17][18][19][20][21][22][23] There are two types of reaction: the first is that drug energy enhanced by light is transferred to biomolecules and free radicals originate on the molecules. The second is that energy is transferred to oxygen, which changes to 1 O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Acid Red 87 (Eosin Y) and C.I. Basic Blue 9 (Methylene Blue) in oxygenated media are defined as effective producers of singlet oxygen [53][54][55][56]. However, the information on the ability of triarylmethane dyes to generate 1 O 2 upon photoexcitation found in literature is not consistent.…”
Section: Singlet Oxygen Production Upon Irradiation Of Dyes Evidencedmentioning
confidence: 99%
“…3 1) Although these dyes have been widely used as food additives for their bright color and stability, it is well known that the dyes with halogen substituents (erythrosine, rose bengal, and phloxine) act as efficient photosensitizers, as observed for porphyrin derivatives. [2][3][4][5][6][7] Under irradiation in aqueous solution, these xanthene dyes support the generation of reactive oxygen species such as singlet molecular oxygen ( 1 O 2 ) and superoxide anion radicals (O 2 − ) by energy transfer and electron transfer processes, respectively. [2][3][4][5][6][7] The strong oxidative action of the reactive oxygen species generated by these processes has been studied for a variety of applications including DNA scission 8) and photodynamic therapy, 9) among others.…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] Under irradiation in aqueous solution, these xanthene dyes support the generation of reactive oxygen species such as singlet molecular oxygen ( 1 O 2 ) and superoxide anion radicals (O 2 − ) by energy transfer and electron transfer processes, respectively. [2][3][4][5][6][7] The strong oxidative action of the reactive oxygen species generated by these processes has been studied for a variety of applications including DNA scission 8) and photodynamic therapy, 9) among others. [10][11][12][13] Many environmental mutagens, such as 3-amino-1,4-dimethyl-5H-pyrido [4,3-b] indole (Trp-P-1), 3-amino-1-methyl-5H-pyrido [4,3-b] indole (Trp-P-2), 2-amino-3-methyl-9H-pyrido [2,3-b] indole (MeAαC), and 2-amino-3-methyl-imidazo [4,5-f ] quinoline (IQ), are known to be present in our surrounding environment and have been identified as human carcinogens.…”
mentioning
confidence: 99%